PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, LEVERAGE, DAN KEPEMILIKAN PUBLIK TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) - Rindawati, Meita Wahyu; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The CSR program is an investment for the company for the sake of growth and sustainability of thecompany and it is no longer seen as a means of cost (cost center) but rather as a means of profit (profit center).The CSR program is also the commitment of the company in order to support the making of sustainabledevelopment. The purposes of this research are: (1) the positive influence of profitability to the disclosure ofCorporate Social Responsibility (CSR) on the manufacturing companies which are listed in Indonesia StockExchange; (2) the positive influence of firm size to the disclosure of Corporate Social Responsibility (CSR) on themanufacturing companies which are listed in Indonesia Stock Exchange; (3) the positive influence of leverage tothe to the disclosure of Corporate Social Responsibility (CSR) on the manufacturing companies which are listedin Indonesia Stock Exchange; (4) ) the positive influence of public ownership to the disclosure of CorporateSocial Responsibility (CSR) on the manufacturing companies which are listed in Indonesia Stock Exchange. Theresults of this research show that: (1) profitability has positive influence to the CSR disclosure index of themanufacturing companies which are listed in Indonesia Stock Exchange; (2) firm size does not have negativeinfluence to the CSR disclosure index of the manufacturing companies which are listed in Indonesia StockExchange; (3) Leverage has negative influence to the CSR disclosure index of the manufacturing companieswhich are listed in Indonesia Stock Exchange; (4) Public Ownership has negative influence to the CSRdisclosure index of the manufacturing companies which are listed in Indonesia Stock Exchange.Keywords: corporate social responsibility, profitability, size, leverage, public ownership